GAMBARAN STATUS GIZI PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) DI RAWAT INAP RSUD ARIFIN ACHMAD PEKANBARU - Gustien Enderina; Adrianison "; Erwin Christianto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTChronic Obstructive Pulmonary Disease (COPD) is a disease that becomes the health problem in Indonesia until now. Nutritional status is a body condition as a result of food consumption and the use of nutrients. COPD may affect the nutritional status and cause malnutrition, otherwise malnutrition may increase the development of COPD. Malnutrition occurs in 25 – 40% of inpatients and was associated with complications, length of hospitalization, and the high morbidity and mortality. This study was using descriptive methods with crossectional approached. The sampling technique used total sampling. The study was held on February – March 2016 with number of sample is 42 patients with COPD at Arifin Achmad Pekanbaru general hospital inpatient. The result of this study is characteristic based on age showed 21 (50,0%) persons were > 65 years old, 35 (83,3%) persons were male. Characteristic based on occupation showed 12 (28,6%) persons were not work, 13 (31,0%) persons had COPD for 1 – 5 years, and 22 (52,4%) persons with good appetite. Nutritional status based on Body Mass Index (BMI) showed 23 (54,76%) persons were underweight. Nutritional status based on MUAC measurement showed 24 (57,14%) persons were risk of malnutrition. The risk of malnutrition based on Malnutrition Universal Screening Tools (MUST) showed 30 (71,43%) persons were high risk category.Keywords: COPD hospital inpatient, nutritional status, Malnutrition Universal Screening Tools (MUST).